Biomarkers for immunotherapy in esophageal cancer - Wang, Xuelian; Wang, Ping; Huang, Xiang; Han, Yanan; Zhang, Pei (Frontiers in Immunology, 2023)
The development of immunotherapy, especially immune-checkpoint inhibitors targeting PD-1/PD-L1, has improved the outcomes of patients with esophageal cancer. However, not all population derives benefit from the agents. Recently, kinds of biomarkers were introduced to predict the response to immunotherapy. However, the effects of these reported biomarkers are controversial and many challenges remain. In this review, we aim to summarize the current clinical evidence and provide a comprehensive understanding of the reported biomarkers. We also discuss the limits of the present biomarkers and propose our own opinions on which viewers’ discretion are advised.